Konsep Dasar Manajemen Sumber Daya Manusia Pendidikan Islam di MDTA Sukma Illahi Canduang - Alhamda, Robi; Sesmiarni, Zulfani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to describe the basic concept of human resource management (HR) in the context of Islamic education applied in MDTA Sukma Illahi Canduang. HR management is an important component in improving the quality of educational institutions, including Madrasah Diniyah Takmiliyah Awaliyah (MDTA), because the success of the institution is greatly influenced by the quality and management of teaching and educational staff. This study uses a quantitative descriptive approach. With Population: All teaching and educational staff at MDTA Sukma Illahi Canduang with data collection techniques distributing the Islamic Education HR Questionnaire (Guttman Scale: Yes/No) and Data Analysis: Data were collected and analyzed by calculating the percentage of each "Yes" answer to the indicators in each HR component. The results of the study indicate that Based on the results of the quantitative descriptive analysis, it can be concluded that overall, MDTA Sukma Illahi Canduang has shown a strong foundation of Islamic values in its human resource management, especially in work culture and moral-based performance assessment. However, significant improvements are still needed in aspects of teacher professional development and welfare systems. Strategic improvement steps must be designed immediately so that the quality of Islamic education provided is increasingly optimal and competitive.